THE EXISTENCE OF HUMAN RIGHTS FOR THE POOR AND ABANDONED CHILDREN IN INDONESIA - Kamil Muhadzib, Raihan; Yusnita, Ummi (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2025)
Human rights are basic principles that protect and respect the freedom, dignity and well being of every individual, regardless of their social, economic or background status. However, in Indonesia, the existence of human rights for the poor and abandoned children is still a controversial and complex issue. The current condition of the poor and abandoned children in Indonesia shows violations of their rights. The poor often face difficulties in accessing education, housing, health services and decent work, all of which are basic rights guaranteed in the constitution. Neglected children are also often victims of physical, psychological, and sexual exploitation, with the lack of protection and protection they receive. The method used in this research is the normative juridical method by examining the law and examining library materials. The results show that the existence of human rights for the poor and abandoned children in Indonesia requires concrete steps. This includes improving access to basic services such as education, housing, and health care, as well as effective law enforcement against perpetrators of violence and exploitation against children. In this regard, it is important for the government, child protection agencies, and Indonesian society to work together to protect the human rights of the poor and abandoned children, ensure justice and welfare for them, and build a more inclusive society.